2021
DOI: 10.1002/mrc.5196
|View full text |Cite
|
Sign up to set email alerts
|

Selenate—An internal chemical shift standard for aqueous 77Se NMR spectroscopy

Abstract: The 77 Se NMR spectra of selenate were studied under various circumstances, such as concentration, pH, temperature, ionic strength, and D 2 O:H 2 O ratio, in order to examine its potential as a water-soluble internal chemical shift standard. The performance of selenate as a chemical shift reference and that of other attempted ones from the literature (dimethyl selenide, tetramethylsilane/TMS, and 3-(trimethylsilyl)propane-1-sulfonate/DSS) was also explored. The uncertainty in the resulting chemical shift relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…77 Se{ 1 H} NMR spectroscopy can be used as a practical tool to follow the redox progress of organoselenium compounds in an easy and direct way. 21 Mechanistic studies of ebselen 1 followed by 77 Se{ 1 H} NMR spectroscopy using thiols such as PhSH or GSH indicated that the Se–N bond is reductively cleaved to form the corresponding selenenyl sulphide intermediate, which further reacted with H 2 O 2 to produce selenol and selenenic acid as highly reactive intermediates. 13 f ,14 Furthermore, it has been demonstrated in phase II for the safety of noise-induced hearing loss and phase III for cerebral ischemia and bipolar disorder diseases.…”
Section: Introductionmentioning
confidence: 99%
“…77 Se{ 1 H} NMR spectroscopy can be used as a practical tool to follow the redox progress of organoselenium compounds in an easy and direct way. 21 Mechanistic studies of ebselen 1 followed by 77 Se{ 1 H} NMR spectroscopy using thiols such as PhSH or GSH indicated that the Se–N bond is reductively cleaved to form the corresponding selenenyl sulphide intermediate, which further reacted with H 2 O 2 to produce selenol and selenenic acid as highly reactive intermediates. 13 f ,14 Furthermore, it has been demonstrated in phase II for the safety of noise-induced hearing loss and phase III for cerebral ischemia and bipolar disorder diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an accurate and practical referencing protocol must be used to properly assign each signal. 57–59 For the 77 Se NMR spectra, different organic compounds (secondary standards) have been employed, 60 because Me 2 Se 60% v/v (primary standard; δ = 0.0 ppm) is volatile, toxic, and has a very bad smell.…”
mentioning
confidence: 99%
“…45–56 Additionally, some 77 Se NMR investigations are performed under different experimental conditions, which could make the assignment of different signals somewhat troublesome because of the effect of the solvent on the chemical shift value. 45–60…”
mentioning
confidence: 99%